coinBD: an enhanced version of proof of work with less computational power - Hossain, Mohammad Badrul; Akash, Sadman Sakib; Haque, Md. Asraful (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.